Recommended Water Tests for Private Wells - Powell, G. Morgan; Bradshaw, Michael H.; Dallemand, Barbara (My University, 1995)
This publication provides recommendations for individuals with private wells, including ways to test the water to ensure it is safe to drink.
MF871_1995_05
Keywords: MF871; Health and Saftey; Home and Family; MF